Aplikasi Mobile dalam Meningkatkan Efektivitas Manajemen Keuangan Pribadi - Marwan Ramdhany Edy; Hidayat Nurwahid; Muhammad Januar Anshari; Aswar; Muh Sahlan Syah (Program Studi Teknik Komputer, 2024)
This research aims to develop a FinanTrack mobile application that assists users in managing personal finances efficiently. This application is developed through several important stages, starting from needs analysis, software design with use case diagrams and data flow diagrams, and implementation using the Java programming language on Android Studio. The FinanTrack application has a main feature to record expenses and income, as well as a form to add new transaction data. Users can categorize transactions, view history, and monitor total finances in real- time. With this application, it is hoped that people can easily manage their personal finances through their smartphones, so as to improve financial literacy and help achieve better financial stability.